DIPLOMASI PUBLIK INDONESIA MELALUI BALI DEMOCRACY FORUM - Yuswari Octonain Djemat (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
Public Diplomacy for a country is an important tool. This study aims to analyze the public diplomacy strategy carried out by Indonesia as a response to the Global War on Terror (GWOT) policy carried out by America after the events of September 11, 2001. Public diplomacy carried out by Indonesia through the Bali Democracy Forum (BDF) is growing. Every year the number of participating countries participating in the BDF continues to increase. Indonesia must be able to take advantage of this momentum and formulate an increasingly comprehensive public diplomacy strategy in order to improve Indonesia's self- image in the eyes of the international community. This study uses qualitative research methods with descriptive research types and secondary data collection through literature studies, such as books, journals, e-books, e- journals, and other internet sources such as from government agencies, ministries, embassies of the Republic of Indonesia (RI) and portals. online news